Radical inclusivity and the journey on the way to somewhere [irgendwohin unterwegs] - Aarde, Andries van (HTS teologiese studies, 2023)
This article represents the genre of auto-ethnographic, autobiographical research. It consists of questions which evoke narrative responses because the questions register a life story in itself. Pieter G.R. de Villiers is the interpellator and Andries G. van Aarde the respondent. They are long-standing friends and both professors of New Testament studies. De Villiers is presently the editor at LitNet Academic (Religious Studies), and Van Aarde is the editor of HTS Theological Studies. Since 1990, De Villiers has been Executive Director of the Centre for Christian Spirituality and Ethics and has been a Research Fellow and Professor Extraordinarius in Biblical Spirituality at the Department of Old and New Testament Studies at the Faculty of Theology, University of the Free State (since 2001).Contribution: The article reflects a conversation between Andries G. van Aarde and Pieter G.R. de Villiers. It contributes to an understanding of contemporary South African church history, including the protest by academics in Afrikaans ecclesial circles against apartheid and gender injustice.